Evaluation Of The Influence Of Learning Media Website On User Satisfaction With PLS-SEM - Nasarudin Sar Afwan; Wing Wahyu Winarno; Mei P Kurniawan (STMIK PONTIANAK, 2022)
The COVID-19 pandemic has changed the way people interact, communicate and work, as well as in the world of education where the learning process is carried out more using online methods. Schools need to prepare a special forum that can be used as an online learning medium. One of them is a learning website. SMKN 2 Kuripan develops a learning media website with the page www.lms.smkn2kuripan.sch.id. This page helps the learning process in schools in blended learning. This research will test the quality of the website that is used to find out whether the website has met user satisfaction or not. It is important to do this as an improvement material for managers on the quality of the website. The test uses SmartPLS with the WebQual 4.0 method approach through question indicators for each variable that are distributed to users for collecting and testing quantitative data.In the SmartPLS test, the results obtained that the variables of usability quality and interaction service quality have a significant and acceptable effect on user satisfaction. While the quality of information is not yet significant. These results are important as material for improvement and evaluation of managers on the results of the answers from which variable indicators have not reached a good category on website quality. For further research suggestions, other evaluation methods can be added such as ServQual, TAM combined with the WebQual method to get more precise evaluation results and it is necessary to do a comparison analysis of other testing tools such as SPSS, WarpPLS, and Amos.